UNIT 4.1 An Introduction to Genome Annotation. Issue 1 (17th December 2015) - Campbell, Michael S.; Yandell, Mark
Abstract : Genome projects have evolved from large international undertakings to tractable endeavors for a single lab. Accurate genome annotation is critical for successful genomic, genetic, and molecular biology experiments. These annotations can be generated using a number of approaches and available software tools. This unit describes methods for genome annotation and a number of software tools commonly used in gene annotation. © 2015 by John Wiley & Sons, Inc.